MUC505 : Music for moving images / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course exposes students to the production techniques of creating music content to fit various video format requirements such as film, animation, broadcast, video-streaming and video games. This introduction to the role of music in film provides students an in-depth understanding of how an effective film score is assembled. Students start the class with watching a short cut-scene and discussion. In some classes, hands-on practical work will be assigned and done during class, ranged from spotting to timing, conceptualizing to simple composing exercises. Towards the end of the course student composers write for simple scenes, record cues, and working with limited budgets.